MONITORING CHANGES IN THE BORDER SPACE OF UKRAINE: MANAGEMENT ASPECT - Torichnyi, Vadym; Melnychuk, Yuriy (Honor and Law, 2023)
Ukraine is not abandoning its European integration course. The foundation of such integration is the reformatting of the Ukrainian social community on the basis of democracy. Transformations should apply to all state entities, and therefore the State Border Service of Ukraine should carry out thorough reforms. The main direction in such reforming is the creation of a system of integrated border management. Constant dynamics are recorded in the border security environment, which confirms the urgency of the need for its regular observation and study. Ukraine’s implementation of the system of integrated border management as a system of principles, methods, means, tools and laws of state management of border security is one of the essential "technical conditions" for its acquisition of a visa-free regime with EU member states and remains one of the necessary conditions for its European integration into in the context of cooperation on issues of justice, freedom and security. The main proposal is to build an effective and comprehensive environment for information exchange based on the Comprehensive European Situational Picture and early warning system, in particular, thanks to the implementation of the EUROSUR system. The modern national regulatory framework and strategic planning documents regarding the introduction of the EUROSUR system were not considered. This fact is confirmed by the limited coverage of this problem in scientific works. The State Border Service of Ukraine is consistently implementing steps for divergent (combined) transformation of the agency in two directions: positioning as a modern European-style law enforcement agency; in the status of a military formation, which is suitable for performing border protection tasks in a special period. The system of guarding and protecting the state border of Ukraine is an integral part of the state-wide system of ensuring national security. Various threats may arise in this system, in particular in its border area.